Experimental and computational flow field studies of an integrally cast cooling manifold with and without rotation - Ieronymidis, I; Gillespie, D; Ireland, P; Kingston, R; ASME (2006)
This paper presents detailed pressure measurements and discharge coefficient data for a long, low aspect ratio manifold; part of a novel blade cooling scheme. The cooling geometry, in which a series of racetrack passages are connected to a central plenum, provides high heat transfer coefficients in regions of the blade in good thermal contact with the outer blade surface. The Reynolds number changes along its length because of the ejection of fluid through a series of 19 transfer holes in a staggered arrangement, which are used to connect ceramic cores during the casting process. For rotation number RN = 0 the velocity down each hole remains almost constant. A correlation between hole discharge coefficient and Velocity Head Ratio is also presented. Pressure loss coefficients in the passage and through the holes are also discussed. A High Pressure (HP) rig was tested to investigate compressibility effects and expand the inlet Reynolds number range. A CFD model was validated against the experimental data, and then used to investigate the effects of rotation on the hole discharge coefficients. Results are presented for an inlet Reynolds number of 43477. At an engine representative rotation number of 0.08 corresponding buoyancy number of 0.17 there was little effect of rotation. However, at high rotational speeds secondary flows in the cooling passage and the exit plenum greatly reduce the hole discharge coefficient by increasing the local cross flow at the hole entrances and capping the hole exits in a manner similar to that seen in leading edge film-cooling geometries. Copyright © 2006 by ASME.